AI , Comparative Advantage, and the Next Decade of Ecological Research - John M. Drake (Ecology Letters, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Evaluating transgenic Darling 54 American chestnuts for reintroduction: Insights from survivorship, growth, and respiration in a common garden - Taylor M. Wegner; Andrew E. Newhouse; Sean Satchwell; John E. Drake (Forest Ecology and Management, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Evaluating restoration candidates: Performance of blight-tolerant American chestnut varieties in open field and shelterwood silvicultural conditions - Jacob A. Olichney; Andrew E. Newhouse; Molly Z. Franklin; Jason A. Holliday; Sara K. Klopf; William A. Powell; Stephen V. Stehman; John E. Drake (Forest Ecology and Management, 2026)

Mechanical site preparation treatment and species effects on carbon pools in 12-year-old American sycamore [Platanus occidentalis L.] and willow oak [Quercus phellos L.] riparian plantations, Virginia Piedmont, USA - Drake H. Lynn; W. Michael Aust; David R. Carter; P. Corey Green; John R. Seiler (New Forests, 2025)
Restoration of riparian forests can improve water quality and wildlife habitat and also sequester carbon. Unfortunately, failures of riparian restoration efforts are common due to planting mortality. Selection of well-suited species, dense planting and use of mechanical soil site preparations may potentially enhance wetland restoration plantings. Carbon valuation of forestland is increasing and additional research is needed to determine rates and pools of carbon accumulation in riparian areas. We evaluated the effects of four soil mechanical site preparation treatments (bedding, disking, pit and mounding, and ripping) and species selection (American sycamore [ Platanus occidentalis L.] and willow oak, [ Quercus phellos L.] on survival, growth and carbon storage across multiple pools: planted trees, herbaceous vegetation, fine roots, organic soil (litter) horizons, and the mineral soil. At 12 years, species selection was more important to carbon storage than site preparation. American sycamore was well-suited to the site and had better survival than willow oak (64% vs. 42% survival). American sycamore also stored more carbon across all site preparation methods than willow oak. Measured carbon storage averaged 74.8 Mg ha −1 for American sycamore treatments and 63.1 Mg ha −1 for willow oak treatments. The densely planted treatments established forests even in higher mortality willow oak plots. Results indicate that appropriate species planted at high densities may be used to enhance forest stand establishment and carbon storage in similar riparian restorations.

Modelling Like an Experimentalist - John M. Drake (Ecology Letters, 2025)
Modelling has become a routine part of ecological and evolutionary research, yet its practice often lacks a clear conceptual framework. I propose that modelling can be fruitfully understood as experimentation. Like empirical studies, modelling projects involve treatments, levels and responses: parameter regimes or data manipulations serve as treatments, replicated runs yield summaries and comparisons across conditions reveal main effects and interactions. This framing sharpens design, reduces mission creep and clarifies communication. I outline common layers of abstraction, highlight good modelling habits and argue that thinking like an experimentalist fosters rigour, reliability and credibility without constraining creativity.

A century of tailings migration from silver mining reduced biodiversity in a Boreal Shield lake - Branaavan Sivarajah; Dale D. Sprague; Drake Hyden; John P. Smol; Joshua Kurek; Jesse C. Vermaire (Environmental Pollution, 2025)

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Scaling of Extinction Time With Habitat Size in Experimental Populations - John M. Drake; Éric Marty; Anurag Sau (Ecology Letters, 2025)
Theoretical models suggest that the mean time to extinction scales with habitat size through either exponential or power law relationships, depending on demographic and environmental stochasticity. Despite extensive theoretical work, empirical validation of these scaling relationships is limited. Here, we report a microcosm study of Daphnia magna populations in experimental chambers consisting of 1, 2, 4, 8, 16, or 32 patches, with a total of 35 populations monitored daily until extinction. We tested the scaling of extinction time with patch count using nonlinear regression models for both exponential and power law functions, comparing model fit with mean squared error. Overall, the data supported the power law over an exponential relationship (bootstrapped ) although the difference between the models is not evident when comparing some treatment levels. Our experiment provides the first empirical test of long‐standing theoretical predictions and lays a foundation for future studies to expand the understanding of extinction dynamics in ecological systems.

Two Hypotheses About Climate Change and Species Distributions - John M. Drake; John P. Wares; James E. Byers; Jill T. Anderson (Ecology Letters, 2025)
Species' distributions are changing around the planet as a result of global climate change. Most research has focused on shifts in mean climate conditions, leaving the effects of increased environmental variability comparatively underexplored. This paper proposes two new macroecological hypotheses—the variability damping hypothesis and the variability adaptation hypothesis —to understand how ecological dynamics and evolutionary history could influence biogeographic patterns being forced by contemporary large‐scale climate change across all major ecosystems. The variability damping hypothesis predicts that distributions of species living in deep water environments will be least affected by increasing climate‐driven temperature variability compared with species in nearshore, intertidal and terrestrial environments. The variability adaptation hypothesis predicts the opposite. Where available, we discuss how the existing evidence aligns with these hypotheses and propose ways in which they may be empirically tested.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Local socioeconomic factors predict urban forest structure and composition across neighborhoods in Syracuse, NY (USA) - Jordan Jessamy; John E. Drake; David J. Nowak; John C. Stella (Landscape and Urban Planning, 2024)

Intrinsic and Extrinsic Regulation of Water Clarity in a Large, Floodplain River Ecosystem - Alicia M. Carhart; Deanne C. Drake; James R. Fischer; Jeffrey N. Houser; Kathi J. Jankowski; John E. Kalas; Eric M. Lund (Ecosystems, 2024)

Propagating Uncertainty in Predicting Individuals and Means Illustrated with Foliar Chemistry and Forest Biomass - Ruth D. Yanai; John E. Drake; Hannah L. Buckley; Bradley S. Case; Paul J. Lilly; Richard C. Woollons; Javier G. P. Gamarra (Ecosystems, 2024)
Quantifying uncertainty is important to establishing the significance of comparisons, to making predictions with known confidence, and to identifying priorities for investment. However, uncertainty can be difficult to quantify correctly. While sampling error is commonly reported based on replicate measurements, the uncertainty in regression models used to estimate forest biomass from tree dimensions is commonly ignored and has sometimes been reported incorrectly, due either to lack of clarity in recommended procedures or to incentives to underestimate uncertainties. Even more rarely are the uncertainty in predicting individuals and the uncertainty in the mean both recognized for their contributions to overall uncertainty. In this paper, we demonstrate the effect of propagating these two sources of uncertainty using a simple example of calcium concentration of sugar maple foliage, which does not require regression, then the mass of foliage and calcium content of foliage, and finally an entire forest with multiple species and tissue types. The uncertainty due to predicting individuals is greater than the uncertainty in the mean for studies with few trees—up to 30 trees for foliar calcium concentration and 50 trees for foliar mass and calcium content in the data set we analyzed from the Hubbard Brook Experimental Forest. The most correct analysis will take both sources of uncertainty into account, but for practical purposes, country-level reports of uncertainty in carbon stocks can safely ignore the uncertainty in individuals, which becomes negligible with large enough numbers of trees. Ignoring the uncertainty in the mean will result in exaggerated confidence in estimates of forest biomass and carbon and nutrient contents.

Proximity to an old-growth forest edge and ectomycorrhizal tree islands enhance ectomycorrhizal fungal colonization of Betula lenta L. (black birch) seedlings in secondary forest soils - Andrew M. Cortese; John E. Drake; Martin Dovciak; Jonathan B. Cohen; Thomas R. Horton (Plant and Soil, 2023)

How to publish a ‘Method’ article in Ecology Letters - John M. Drake (Ecology Letters, 2023)

Scaling up uncertainties in allometric models: How to see the forest, not the trees - Jian Lin; Javier G.P. Gamarra; John E. Drake; Anibal Cuchietti; Ruth D. Yanai (Forest Ecology and Management, 2023)

From raw data to publication: Introducing data editing at Ecology Letters - Peter H. Thrall; Jonathan Chase; John Drake; Nathalie Espuno; Stephane Hello; Vanessa Ezenwa; Barbara Han; Akira Mori; Helene Muller‐Landau (Ecology Letters, 2023)

Comparative growth and physiological performance of American chestnuts, oaks, hickories, and sugar maple across a silvicultural gradient in overstory retention - Garrett R. Evans; Julia I. Burton; William A. Powell; John E. Drake (Forest Ecology and Management, 2023)

Forecast Sensitivity-based Observation Impact (FSOI) in an analysis–forecast system of the California Current Circulation - Patrick Drake; Christopher A. Edwards; Hernan G. Arango; John Wilkin; Tayebeh TajalliBakhsh; Brian Powell; Andrew M. Moore (Ocean Modelling, 2023)

Disasters collide at the intersection of extreme weather and infectious diseases - John M. Drake; Éric Marty; Kamal J. K. Gandhi; Meredith Welch‐Devine; Brian Bledsoe; Marshall Shepherd; Lynne Seymour; Christine C. Fortuin; Cristian Montes (Ecology Letters, 2023)
Natural disasters interact to affect the resilience and prosperity of communities and disproportionately affect low income families and communities of colour. However, due to lack of a common theoretical framework, these are rarely quantified. Observing severe weather events (e.g. hurricanes and tornadoes) and epidemics (e.g. COVID‐19) unfolding in southeastern US communities led us to conjecture that interactions among catastrophic disturbances might be much more considerable than previously recognized. For instance, hurricane evacuations increase human aggregation, a factor that affects the transmission of acute infections like SARS‐CoV‐2. Similarly, weather damage to health infrastructure can reduce a community's ability to provide services to people who are ill. As globalization and human population and movement continue to increase and weather events are becoming more intense, such complex interactions are expected to magnify and significantly impact environmental and human health.

Oxalate oxidase transgene expression in American chestnut leaves has little effect on photosynthetic or respiratory physiology - Anuli Onwumelu; William A. Powell; Andrew E. Newhouse; Garrett Evans; Gwen Hilles; Dakota F. Matthews; Vernon Coffey; John E. Drake (New Forests, 2023)

How to publish a ‘perspective’ or ‘synthesis’ article in Ecology Letters - John M. Drake; Jonathan M. Chase (Ecology Letters, 2023)

Season and prey identity mediate the effect of predators on parasites in rodents: a test of the healthy herds hypothesis - Robert L. Richards; L. Mike Conner; Gail Morris; John M. Drake; Vanessa O. Ezenwa (Oecologia, 2023)

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Do predators keep prey healthy or make them sicker? A meta‐analysis - Robert L. Richards; John M. Drake; Vanessa O. Ezenwa (Ecology Letters, 2022)
Ecological theory suggests that predators can either keep prey populations healthy by reducing parasite burdens or alternatively, increase parasitism in prey. To quantify the overall magnitude and direction of the effect of predation on parasitism in prey observed in practice, we conducted a meta‐analysis of 47 empirical studies. We also examined how study attributes, including parasite type and life cycle, habitat type, study design, and whether predators were able to directly consume prey contributed to variation in the predator‐prey‐parasite interaction. We found that the overall effect of predation on parasitism differed between parasites and parasitoids and that whether consumptive effects were present, and whether a predator was a non‐host spreader of parasites, were the most important traits predicting the parasite response. Our results suggest that the mechanistic basis of predator‐prey interactions strongly influences the effects of predators on parasites and that these effects, although context dependent, are predictable.

Understanding Constraints on Submersed Vegetation Distribution in a Large, Floodplain River: the Role of Water Level Fluctuations, Water Clarity and River Geomorphology - Alicia M. Carhart; John E. Kalas; James T. Rogala; Jason J. Rohweder; Deanne C. Drake; Jeffrey N. Houser (Wetlands, 2021)

Friend or foe? The role of biotic agents in drought-induced plant mortality - Robert J. Griffin-Nolan; Neha Mohanbabu; Sarah Araldi-Brondolo; Alexander R. Ebert; Julie LeVonne; Joanna I. Lumbsden-Pinto; Hannah Roden; Jordan R. Stark; Jordon Tourville; Katie M. Becklin; John E. Drake; Douglas A. Frank; et al. (Plant Ecology, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Integrating data mining and transmission theory in the ecology of infectious diseases - Barbara A. Han; Suzanne M. O’Regan; John Paul Schmidt; John M. Drake (Ecology Letters, 2020)
Our understanding of ecological processes is built on patterns inferred from data. Applying modern analytical tools such as machine learning to increasingly high dimensional data offers the potential to expand our perspectives on these processes, shedding new light on complex ecological phenomena such as pathogen transmission in wild populations. Here, we propose a novel approach that combines data mining with theoretical models of disease dynamics. Using rodents as an example, we incorporate statistical differences in the life history features of zoonotic reservoir hosts into pathogen transmission models, enabling us to bound the range of dynamical phenomena associated with hosts, based on their traits. We then test for associations between equilibrium prevalence, a key epidemiological metric and data on human outbreaks of rodent‐borne zoonoses, identifying matches between empirical evidence and theoretical predictions of transmission dynamics. We show how this framework can be generalized to other systems through a rubric of disease models and parameters that can be derived from empirical data. By linking life history components directly to their effects on disease dynamics, our mining‐modelling approach integrates machine learning and theoretical models to explore mechanisms in the macroecology of pathogen transmission and their consequences for spillover infection to humans.

The temperature optima for tree seedling photosynthesis and growth depend on water inputs - Dushan P. Kumarathunge; John E. Drake; Mark G. Tjoelker; Rosana López; Sebastian Pfautsch; Angelica Vårhammar; Belinda E. Medlyn (Global Change Biology, 2020)
Understanding how tree growth is affected by rising temperature is a key to predicting the fate of forests in future warmer climates. Increasing temperature has direct effects on plant physiology, but there are also indirect effects of increased water limitation because evaporative demand increases with temperature in many systems. In this study, we experimentally resolved the direct and indirect effects of temperature on the response of growth and photosynthesis of the widely distributed species Eucalyptus tereticornis . We grew E. tereticornis in an array of six growth temperatures from 18 to 35.5°C, spanning the climatic distribution of the species, with two watering treatments: (a) water inputs increasing with temperature to match plant demand at all temperatures ( W incr ), isolating the direct effect of temperature; and (b) water inputs constant for all temperatures, matching demand for coolest grown plants ( W const ), such that water limitation increased with growth temperature. We found that constant water inputs resulted in a reduction of temperature optima for both photosynthesis and growth by ~3°C compared to increasing water inputs. Water limitation particularly reduced the total amount of leaf area displayed at T opt and intermediate growth temperatures. The reduction in photosynthesis could be attributed to lower leaf water potential and consequent stomatal closure. The reduction in growth was a result of decreased photosynthesis, reduced total leaf area display and a reduction in specific leaf area. Water availability had no effect on the response of stem and root respiration to warming, but we observed lower leaf respiration rates under constant water inputs compared to increasing water inputs at higher growth temperatures. Overall, this study demonstrates that the indirect effect of increasing water limitation strongly modifies the potential response of tree growth to rising global temperatures.

An extreme heatwave enhanced the xanthophyll de-epoxidation state in leaves of Eucalyptus trees grown in the field - Namraj Dhami; John E. Drake; Mark G. Tjoelker; David T. Tissue; Christopher I. Cazzonelli (Physiology and Molecular Biology of Plants, 2020)

Determining the Sources of Variance in the Preparation of Analytical Standards for Chromatographic Analysis of a Lyophilized Peptide Drug Substance by Nested ANOVA Statistical Analysis - Paul L. Walsh; John Lena; Jennifer Drake; David Lavrich (AAPS PharmSciTech, 2020)

Fusarium solani haplotype 12‐b and aortic and branchial arteritis in Hippocampus erectus Perry - Tori Brown; Zach Millar; Drake Evans; Phuc H. Pham; Veronique LePage; John S. Lumsden (Journal of Fish Diseases, 2020)

Indigenous knowledge for seasonal weather and climate forecasting across East Africa - Maren Radeny; Ayal Desalegn; Drake Mubiru; Florence Kyazze; Henry Mahoo; John Recha; Philip Kimeli; Dawit Solomon (Climatic Change, 2019)

Contrasting latitudinal gradients of body size in helminth parasites and their hosts - Tad Dallas; Alyssa‐Lois M. Gehman; A. Alonso Aguirre; Sarah A. Budischak; John M. Drake; Maxwell J. Farrell; Ria Ghai; Shan Huang; Ignacio Morales‐Castilla (Global Ecology and Biogeography, 2019)
Aim We examined body size scaling relationships for two developmental life stages of parasitic helminths (egg and adult) separately in relationship to latitude (i.e. Bergmann's rule), temperature and temperature seasonality. Given that helminth eggs experience environmental conditions more directly, whereas adults live inside infected host individuals, we predict stronger environmentally driven gradients of body size for eggs than for adults. Location Global. Time period Present day. Major taxa studied Parasitic helminths. Methods We compiled egg size and adult body size data (both minimum and maximum) for 265 parasitic helminth species from the literature, along with species latitudinal distribution information using an extensive global helminth occurrence database. We then examined how the average helminth egg and adult body size of all helminth species present (minimum and maximum separately) scaled with latitude, temperature and temperature variability, using generalized linear models. Results Both the egg size and the adult body size of helminths tended to decrease towards higher latitudes, although we found the opposite body size scaling pattern for their host species. Helminth sizes were also positively correlated with temperature and negatively, but more weakly, with temperature seasonality. Main conclusions Instead of following the body size patterns of their hosts, helminth parasites are more similar to other ectotherms in that they follow the converse Bergmann's rule. This pattern did not differ between helminth developmental stages, suggesting that mean annual temperature and seasonality are unlikely to be related mechanistically to body size variation in this case.

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

Disentangling reporting and disease transmission - Eamon B. O’Dea; John M. Drake (Theoretical Ecology, 2019)

Photosynthetic capacity and leaf nitrogen decline along a controlled climate gradient in provenances of two widely distributed Eucalyptus species - Kristine Y. Crous; John E. Drake; Michael J. Aspinwall; Robert E. Sharwood; Mark G. Tjoelker; Oula Ghannoum (Global Change Biology, 2018)
Climate is an important factor limiting tree distributions and adaptation to different thermal environments may influence how tree populations respond to climate warming. Given the current rate of warming, it has been hypothesized that tree populations in warmer, more thermally stable climates may have limited capacity to respond physiologically to warming compared to populations from cooler, more seasonal climates. We determined in a controlled environment how several provenances of widely distributed Eucalyptus tereticornis and E. grandis adjusted their photosynthetic capacity to +3.5°C warming along their native distribution range (~16–38°S) and whether climate of seed origin of the provenances influenced their response to different growth temperatures. We also tested how temperature optima ( T opt ) of photosynthesis and J max responded to higher growth temperatures. Our results showed increased photosynthesis rates at a standardized temperature with warming in temperate provenances, while rates in tropical provenances were reduced by about 40% compared to their temperate counterparts. Temperature optima of photosynthesis increased as provenances were exposed to warmer growth temperatures. Both species had ~30% reduced photosynthetic capacity in tropical and subtropical provenances related to reduced leaf nitrogen and leaf Rubisco content compared to temperate provenances. Tropical provenances operated closer to their thermal optimum and came within 3% of the T opt of J max during the daily temperature maxima. Hence, further warming may negatively affect C uptake and tree growth in warmer climates, whereas eucalypts in cooler climates may benefit from moderate warming.

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

New innovations for 2018 and beyond - Tim Coulson; Peter Thrall; Jon Chase; Helmut Hillebrand; Vanessa Ezenwa; John Drake; Nathalie Espuno; Stephane Hello (Ecology Letters, 2018)

Locust displacing winds in eastern Australia reassessed with observations from an insect monitoring radar - Zhenhua Hao; V. Alistair Drake; Leesa Sidhu; John R. Taylor (International Journal of Biometeorology, 2017)

A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.

Rhizosphere-driven increase in nitrogen and phosphorus availability under elevated atmospheric CO2 in a mature Eucalyptus woodland - Raúl Ochoa-Hueso; John Hughes; Manuel Delgado-Baquerizo; John E. Drake; Mark G. Tjoelker; Juan Piñeiro; Sally A. Power (Plant and Soil, 2017)

Time to extinction in deteriorating environments - Katherine Zarada; John M. Drake (Theoretical Ecology, 2017)

When can the cause of a population decline be determined? - Trevor J. Hefley; Mevin B. Hooten; John M. Drake; Robin E. Russell; Daniel P. Walsh (Ecology Letters, 2016)
Inferring the factors responsible for declines in abundance is a prerequisite to preventing the extinction of wild populations. Many of the policies and programmes intended to prevent extinctions operate on the assumption that the factors driving the decline of a population can be determined. Exogenous factors that cause declines in abundance can be statistically confounded with endogenous factors such as density dependence. To demonstrate the potential for confounding, we used an experiment where replicated populations were driven to extinction by gradually manipulating habitat quality. In many of the replicated populations, habitat quality and density dependence were confounded, which obscured causal inference. Our results show that confounding is likely to occur when the exogenous factors that are driving the decline change gradually over time. Our study has direct implications for wild populations, because many factors that could drive a population to extinction change gradually through time.

Leading indicators of mosquito-borne disease elimination - Suzanne M. O’Regan; Jonathan W. Lillie; John M. Drake (Theoretical Ecology, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Competition‐mediated feedbacks in experimental multispecies epizootics - Tad Dallas; Richard J. Hall; John M. Drake (Ecology, 2016)
Competition structures ecological communities and alters host–pathogen interactions. In environmentally transmitted pathogens, an infection‐resistant competitor may influence infection dynamics in a susceptible species through the negative impacts of competition (e.g., by reducing host density or causing nutritional stress that increases susceptibility to infection) and/or the positive impacts of reducing transmission efficiency (e.g., by removing environmental pathogen stages). Thus, a non‐susceptible competitor may enhance, reduce, or have no net effect on susceptible host density and infection prevalence. Here, we couple an epidemiological model with experimental epidemics to test how resource competition with a non‐susceptible competitor ( Daphnia pulicaria ) influences fungal microparasite ( Metschnikowia bicuspidata ) infection dynamics in a susceptible host species ( D. dentifera ). Our model and experiments suggest that competitor density can mediate the direction and magnitude of the effect of competition on infection dynamics, with a peak in infection prevalence occurring at intermediate competitor densities. At low densities, the non‐susceptible competitor D. pulicaria may reduce infection prevalence in the susceptible host by removing fungal spores from the environment through feeding. However, when competitor density is increased and resources become limiting, D. pulicaria negatively impacts the susceptible host by increasing susceptible host feeding rates, and therefore fungal spore intake, and further by reducing susceptible host population size as it is driven toward competitive exclusion. In conclusion, these results show that a tradeoff between the competitor as a consumer of pathogen, which serves to reduce epidemic size, and as a modifier of susceptible host foraging ecology, which influences infection rates, may alternately enhance or dampen the magnitude of local epidemics.

Short‐term carbon cycling responses of a mature eucalypt woodland to gradual stepwise enrichment of atmospheric CO 2 concentration - John E. Drake; Catriona A. Macdonald; Mark G. Tjoelker; Kristine Y. Crous; Teresa E. Gimeno; Brajesh K. Singh; Peter B. Reich; Ian C. Anderson; David S. Ellsworth (Global Change Biology, 2016)
Projections of future climate are highly sensitive to uncertainties regarding carbon (C) uptake and storage by terrestrial ecosystems. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment was established to study the effects of elevated atmospheric CO 2 concentrations (eCO 2 ) on a native mature eucalypt woodland with low fertility soils in southeast Australia. In contrast to other FACE experiments, the concentration of CO 2 at Euc FACE was increased gradually in steps above ambient (+0, 30, 60, 90, 120, and 150 ppm CO 2 above ambient of ~400 ppm), with each step lasting approximately 5 weeks. This provided a unique opportunity to study the short‐term (weeks to months) response of C cycle flux components to eCO 2 across a range of CO 2 concentrations in an intact ecosystem. Soil CO 2 efflux (i.e., soil respiration or R soil ) increased in response to initial enrichment (e.g., +30 and +60 ppm CO 2 ) but did not continue to increase as the CO 2 enrichment was stepped up to higher concentrations. Light‐saturated photosynthesis of canopy leaves ( A sat ) also showed similar stimulation by elevated CO 2 at +60 ppm as at +150 ppm CO 2 . The lack of significant effects of eCO 2 on soil moisture, microbial biomass, or activity suggests that the increase in R soil likely reflected increased root and rhizosphere respiration rather than increased microbial decomposition of soil organic matter. This rapid increase in R soil suggests that under eCO 2, additional photosynthate was produced, transported belowground, and respired. The consequences of this increased belowground activity and whether it is sustained through time in mature ecosystems under eCO 2 are a priority for future research.

Erratum to: Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Immigration can destabilize tri-trophic interactions: implications for conservation of top predators - Kevin L. S. Drury; Jesse D. Suter; Jacob B. Rendall; Andrew M. Kramer; John M. Drake (Theoretical Ecology, 2015)

Evidence for the persistence of food web structure after amphibian extirpation in a Neotropical stream - Thomas R. Barnum; John M. Drake; Checo Colón-Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; Catherine M. Pringle (Ecology, 2015)
Species losses are predicted to simplify food web structure, and disease‐driven amphibian declines in Central America offer an opportunity to test this prediction. Assessment of insect community composition, combined with gut content analyses, was used to generate periphyton–insect food webs for a Panamanian stream, both pre‐ and post‐amphibian decline. We then used network analysis to assess the effects of amphibian declines on food web structure. Although 48% of consumer taxa, including many insect taxa, were lost between pre‐ and post‐amphibian decline sampling dates, connectance declined by less than 3%. We then quantified the resilience of food web structure by calculating the number of expected cascading extirpations from the loss of tadpoles. This analysis showed the expected effects of species loss on connectance and linkage density to be more than 60% and 40%, respectively, than were actually observed. Instead, new trophic linkages in the post‐decline food web reorganized the food web topology, changing the identity of “hub” taxa, and consequently reducing the effects of amphibian declines on many food web attributes. Resilience of food web attributes was driven by a combination of changes in consumer diets, particularly those of insect predators, as well as the appearance of generalist insect consumers, suggesting that food web structure is maintained by factors independent of the original trophic linkages.

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Tail probabilities of extinction time in a large number of experimental populations - John M. Drake (Ecology, 2014)
Determining the distribution of population extinction times is a fundamental problem in theoretical population biology. In particular, the tail properties, patterns in the probability of long‐term persistence, have not been studied. Further, until now there have been no experimental or observational data sets with which to empirically test the “rare event” predictions of the standard stochastic theory of extinction, which holds that extinction times should be exponentially distributed. I performed an experimental study of extinction in a large number of replicate ( n = 1076) laboratory populations of the waterflea Daphnia pulicaria . Observed extinction time ranged from 1 to 1239 days. Statistical models supported the hypothesis of a power‐law distribution over the exponential distribution and other alternatives. This pattern contradicts the notion that population extinction time has an exponential tail, questioning its ubiquitous use in theoretical ecology. It is also a rare instance of a data set that exhibits power‐law scaling under appropriate statistical criteria.

Direct and indirect effects of elevated atmospheric CO 2 on net ecosystem production in a Chesapeake Bay tidal wetland - John E. Erickson; Gary Peresta; Kathryn J. Montovan; Bert G. Drake (Global Change Biology, 2013)
The rapid increase in atmospheric CO 2 concentrations ( C a ) has resulted in extensive research efforts to understand its impact on terrestrial ecosystems, especially carbon balance. Despite these efforts, there are relatively few data comparing net ecosystem exchange of CO 2 between the atmosphere and the biosphere ( NEE ), under both ambient and elevated C a . Here we report data on annual sums of CO 2 ( NEE net ) for 19 years on a Chesapeake Bay tidal wetland for S cirpus olneyi (C 3 photosynthetic pathway)‐ and Spartina patens (C 4 photosynthetic pathway)‐dominated high marsh communities exposed to ambient and elevated C a (ambient + 340 ppm). Our objectives were to (i) quantify effects of elevated C a on seasonally integrated CO 2 assimilation ( NEE net = NEE day + NEE night , kg C m −2 y −1 ) for the two communities; and (ii) quantify effects of altered canopy N content on ecosystem photosynthesis and respiration. Across all years, NEE net averaged 1.9 kg m −2 y −1 in ambient C a and 2.5 kg m −2 y −1 in elevated C a , for the C 3 ‐dominated community. Similarly, elevated C a significantly ( P 4 ‐dominated community, as NEE net averaged 1.5 kg m −2 y −1 in ambient C a and 1.7 kg m −2 y −1 in elevated C a . This resulted in an average CO 2 stimulation of 32% and 13% of seasonally integrated NEE net for the C 3 ‐ and C 4 ‐dominated communities, respectively. Increased NEE day was correlated with increased efficiencies of light and nitrogen use for net carbon assimilation under elevated C a , while decreased NEE night was associated with lower canopy nitrogen content. These results suggest that rising C a may increase carbon assimilation in both C 3 ‐ and C 4 ‐dominated wetland communities. The challenge remains to identify the fate of the assimilated carbon.

Theory of early warning signals of disease emergenceand leading indicators of elimination - Suzanne M. O’Regan; John M. Drake (Theoretical Ecology, 2013)

Mechanistic analogy: how microcosms explain nature - John M. Drake; Andrew M. Kramer (Theoretical Ecology, 2012)

Impact of a reduced winter snowpack on litter arthropod abundance and diversity in a northern hardwood forest ecosystem - Pamela H. Templer; Andrew F. Schiller; Nathan W. Fuller; Anne M. Socci; John L. Campbell; John E. Drake; Thomas H. Kunz (Biology and Fertility of Soils, 2012)

The Prevalence of Fentanyl in Drug-Related Deaths in Philadelphia 2004–2006 - Stella C. Wong; Lisa Mundy; Rebecca Drake; John A. Curtis; William E. Wingert (Journal of Medical Toxicology, 2010)

Evapotranspiration and water use efficiency in a Chesapeake Bay wetland under carbon dioxide enrichment - JIAHONG LI; JOHN E. ERICKSON; GARY PERESTA; BERT G. DRAKE (Global Change Biology, 2010)
Wetlands evapotranspire more water than other ecosystems, including agricultural, forest and grassland ecosystems. However, the effects of elevated atmospheric carbon dioxide (CO 2 ) concentration ( C a ) on wetland evapotranspiration (ET) are largely unknown. Here, we present data on 12 years of measurements of ET, net ecosystem CO 2 exchange (NEE), and ecosystem water use efficiency (EWUE, i.e. NEE/ET) at 13:00–15:00 hours in July and August for a Scirpus olneyi (C3 sedge) community and a Spartina patens (C4 grass) community exposed to ambient and elevated (ambient+340 μmol mol −1 ) C a in a Chesapeake Bay wetland. Although a decrease in stomatal conductance at elevated C a in the S. olneyi community was counteracted by an increase in leaf area index (LAI) to some extend, ET was still reduced by 19% on average over 12 years. In the S. patens community, LAI was not affected by elevated C a and the reduction of ET was 34%, larger than in the S. olneyi community. For both communities, the relative reduction in ET by elevated C a was directly proportional to precipitation due to a larger reduction in stomatal conductance in the control plants as precipitation decreased. NEE was stimulated about 36% at elevated C a in the S. olneyi community but was not significantly affected by elevated C a in S. patens community. A negative correlation between salinity and precipitation observed in the field indicated that precipitation affected ET through altered salinity and interacted with growth C a . This proposed mechanism was supported by a greenhouse study that showed a greater C a effect on ET in controlled low salinity conditions compared with high salinity. In spite of the differences between the two communities in their responses to elevated C a , EWUE was increased about 83% by elevated C a in both the S. olneyi and S. patens communities. These findings suggest that rising C a could have significant impacts on the hydrologic cycles of coastal wetlands.

Profiling ecosystem vulnerability to invasion by zebra mussels with support vector machines - John M. Drake; Jonathan M. Bossenbroek (Theoretical Ecology, 2009)

Speed of expansion and extinction in experimental populations - John M. Drake; Blaine D. Griffen (Ecology Letters, 2009)
Although the causes of population extinction are well understood, the speed at which populations decline to extinction is not. A testable, counter‐intuitive prediction of stochastic population theory is that, on average, for any interior interval of the domain of biologically attainable population sizes, the expected duration of increase equals the expected duration of decline. Here we report the first empirical tests of this hypothesis. Using data from two experiments in which replicate populations of Daphnia magna were observed to go extinct under different experimental conditions, we failed to reject the null hypothesis of no difference between the growth and decline phases in populations under constant conditions and conditions with modest environmental variability, but find strong evidence to reject equal first passage time in highly variable environments. These results confirm the prediction of equal passage times entailed by diffusion models of population dynamics, supporting continued application in both population theory and conservation decision making under the restricted conditions where the approximation can be expected to hold.

Potential health impacts of heavy-metal exposure at the Tar Creek Superfund site, Ottawa County, Oklahoma - John S. Neuberger; Stephen C. Hu; K. David Drake; Rebecca Jim (Environmental Geochemistry and Health, 2009)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

An oxygen‐mediated positive feedback between elevated carbon dioxide and soil organic matter decomposition in a simulated anaerobic wetland - AMELIA A. WOLF; BERT G. DRAKE; JOHN E. ERICKSON; J. PATRICK MEGONIGAL (Global Change Biology, 2007)
We examined the effects of elevated atmospheric CO 2 on soil carbon decomposition in an experimental anaerobic wetland system. Pots containing either bare C 4 ‐derived soil or the C 3 sedge Scirpus olneyi planted in C 4 ‐derived soil were incubated in greenhouse chambers at either ambient or twice‐ambient atmospheric CO 2 . We measured CO 2 flux from each pot, quantified soil organic matter (SOM) mineralization using δ 13 C, and determined root and shoot biomass. SOM mineralization increased in response to elevated CO 2 by 83–218% ( P P = 0.003). Our results (1) show that there is a positive feedback between elevated atmospheric CO 2 concentrations and wetland SOM decomposition and (2) suggest that this process is mediated by the release of oxygen from the roots of wetland plants. Because this feedback may occur in any wetland system, including peatlands, these results suggest a limitation on the size of the carbon sink presented by anaerobic wetland soils in a future elevated‐CO 2 atmosphere.

Forest carbon use efficiency: is respiration a constant fraction of gross primary production? - EVAN H. DeLUCIA; JOHN E. DRAKE; RICHARD B. THOMAS; MIQUEL GONZALEZ‐MELER (Global Change Biology, 2007)
Carbon‐use efficiency (CUE), the ratio of net primary production (NPP) to gross primary production (GPP), describes the capacity of forests to transfer carbon (C) from the atmosphere to terrestrial biomass. It is widely assumed in many landscape‐scale carbon‐cycling models that CUE for forests is a constant value of ∼0.5. To achieve a constant CUE, tree respiration must be a constant fraction of canopy photosynthesis. We conducted a literature survey to test the hypothesis that CUE is constant and universal among forest ecosystems. Of the 60 data points obtained from 26 papers published since 1975, more than half reported values of GPP that were not estimated independently from NPP; values of CUE calculated from independent estimates of GPP were greater than those calculated from estimates of GPP derived from NPP. The slope of the relationship between NPP and GPP for all forests was 0.53, but values of CUE varied from 0.23 to 0.83 for different forest types. CUE decreased with increasing age, and a substantial portion of the variation among forest types was caused by differences in stand age. When corrected for age the mean value of CUE was greatest for temperate deciduous forests and lowest for boreal forests. CUE also increased as the ratio of leaf mass‐to‐total mass increased. Contrary to the assumption of constancy, substantial variation in CUE has been reported in the literature. It may be inappropriate to assume that respiration is a constant fraction of GPP as adhering to this assumption may contribute to incorrect estimates of C cycles. A 20% error in current estimates of CUE used in landscape models (i.e. ranging from 0.4 to 0.6) could misrepresent an amount of C equal to total anthropogenic emissions of CO 2 when scaled to the terrestrial biosphere.

Fecundity as a Basis for Risk Assessment of Nonindigenous Freshwater Molluscs - REUBEN P. KELLER; JOHN M. DRAKE; DAVID M. LODGE (Conservation Biology, 2007)
The most efficient way to reduce future damages from nonindigenous species is to prevent the introduction of harmful species. Although ecologists have long sought to predict the identity of such species, recent methodological advances promise success where previous attempts failed. We applied recently developed risk assessment approaches to nonindigenous freshwater molluscs at two geographic scales: the Laurentian Great Lakes basin and the 48 contiguous states of the United States. We used data on natural history and biogeography to discriminate between established freshwater molluscs that are benign and those that constitute nuisances (i.e., cause environmental and/or economic damage). Two statistical techniques, logistic regression and categorical tree analysis, showed that nuisance status was positively associated with fecundity. Other aspects of natural history and biogeography did not significantly affect likelihood of becoming a nuisance. We then used the derived statistical models to predict the chance that 15 mollusc species not yet in natural ecosystems would cause damage if they become established. We also tested whether time since establishment is related to the likelihood that nonindigenous mollusc species in the Great Lakes and United States would cause negative impacts. No significant relationship was evident at the U.S. scale, but recently established molluscs within the Great Lakes were more likely to cause negative impacts. This may reflect changing environmental conditions, changing patterns of trade, or may be an indication of “invasional meltdown.” Our quantitative analyses could be extended to other taxa and ecosystems and offer a number of improvements over the qualitative risk assessments currently used by U.S. (and other) government agencies.

Salinity and sea level mediate elevated CO 2 effects on C 3 –C 4 plant interactions and tissue nitrogen in a Chesapeake Bay tidal wetland - JOHN E. ERICKSON; J. PATRICK MEGONIGAL; GARY PERESTA; BERT G. DRAKE (Global Change Biology, 2007)
Elevated atmospheric carbon dioxide concentrations ([CO 2 ]) generally increase plant photosynthesis in C 3 species, but not in C 4 species, and reduce stomatal conductance in both C 3 and C 4 plants. In addition, tissue nitrogen concentration ([N]) often fails to keep pace with enhanced carbon gain under elevated CO 2 , particularly in C 3 species. While these responses are well documented in many species, implications for plant growth and nutrient cycling in native ecosystems are not clear. Here we present data on 18 years of measurement of above and belowground biomass, tissue [N] and total standing crop of N for a Scirpus olneyi ‐dominated (C 3 sedge) community, a Spartina patens ‐dominated (C 4 grass) community and a C 3 –C 4 ‐mixed species community exposed to ambient and elevated (ambient +340 ppm) atmospheric [CO 2 ] in natural salinity and sea level conditions of a Chesapeake Bay wetland. Increased biomass production (shoots plus roots) under elevated [CO 2 ] in the S. olneyi ‐dominated community was sustained throughout the study, averaging approximately 35%, while no significant effect of elevated [CO 2 ] was found for total biomass in the C 4 ‐dominated community. We found a significant decline in C 4 biomass (correlated with rising sea level) and a concomitant increase in C 3 biomass in the mixed community. This shift from C 4 to C 3 was accelerated by the elevated [CO 2 ] treatment. The elevated [CO 2 ] stimulation of total biomass accumulation was greatest during rainy, low salinity years: the average increase above the ambient treatment during the three wettest years (1994, 1996, 2003) was 2.9 t ha −1 but in the three driest years (1995, 1999, 2002), it was 1.2 t ha −1 . Elevated [CO 2 ] depressed tissue [N] in both species, but especially in the S. olneyi where the relative depression was positively correlated with salinity and negatively related with the relative enhancement of total biomass production. Thus, the greatest amount of carbon was added to the S. olneyi ‐dominated community during years when shoot [N] was reduced the most, suggesting that the availability of N was not the most or even the main limitation to elevated [CO 2 ] stimulation of carbon accumulation in this ecosystem.

Demographic Stochasticity, Environmental Variability, and Windows of Invasion Risk for Bythotrephes Longimanus in North America - John M. Drake; Kevin L. S. Drury; David M. Lodge; Agnes Blukacz; N. D. Yan; Greg Dwyer (Biological Invasions, 2006)

Rapid root closure after fire limits fine root responses to elevated atmospheric CO 2 in a scrub oak ecosystem in central Florida, USA - FRANK P. DAY; DANIEL B. STOVER; ALISHA L. PAGEL; BRUCE A. HUNGATE; JOHN J. DILUSTRO; BRANDON T. HERBERT; BERT G. DRAKE; CHARLES R. HINKLE (Global Change Biology, 2006)
Elevated atmospheric carbon dioxide (CO 2 ) often stimulates the growth of fine roots, yet there are few reports of responses of intact root systems to long‐term CO 2 exposure. We investigated the effects of elevated CO 2 on fine root growth using open top chambers in a scrub oak ecosystem at Kennedy Space Center, Florida for more than 7 years. CO 2 enrichment began immediately after a controlled burn, which simulated the natural disturbance that occurs in this system every 10–15 years. We hypothesized that (1) root abundance would increase in both treatments as the system recovered from fire; (2) elevated CO 2 would stimulate root growth; and (3) elevated CO 2 would alter root distribution. Minirhizotron tubes were used to measure fine root length density (mm cm −2 ) every three months. During the first 2 years after fire recovery, fine root abundance increased in all treatments and elevated CO 2 significantly enhanced root abundance, causing a maximum stimulation of 181% after 20 months. The CO 2 stimulation was initially more pronounced in the top 10 cm and 38–49 cm below the soil surface. However, these responses completely disappeared during the third year of experimental treatment: elevated CO 2 had no effect on root abundance or on the depth distribution of fine roots during years 3–7. The results suggest that, within a few years following fire, fine roots in this scrub oak ecosystem reach closure, defined here as a dynamic equilibrium between production and mortality. These results further suggest that elevated CO 2 hastens root closure but does not affect maximum root abundance. Limitation of fine root growth by belowground resources – particularly nutrients in this nutrient‐poor soil – may explain the transient response to elevated CO 2 .

Allee Effects, Propagule Pressure and the Probability of Establishment: Risk Analysis for Biological Invasions - John M. Drake; David M. Lodge (Biological Invasions, 2006)

Antagonistic effects of seed dispersal and herbivory on plant migration - Mark Vellend; Tiffany M. Knight; John M. Drake (Ecology Letters, 2006)
The two factors that determine plant migration rates – seed dispersal and population growth – are generally treated independently, despite the fact that many animals simultaneously enhance plant migration rate via seed dispersal, and decrease it via negative effects of herbivory on population growth. Using extensive empirical data, we modelled the antagonistic effects of seed dispersal and herbivory by white‐tailed deer on potential migration rates of Trillium grandiflorum , a forest herb in eastern North America. This novel antagonistic interaction is illustrated by maximum migration rates occurring at intermediate, but low herbivory (

Invasion in space and time: non‐native species richness and relative abundance respond to interannual variation in productivity and diversity - Elsa E. Cleland; Melinda D. Smith; Sandy J. Andelman; Christy Bowles; Karen M. Carney; M. Claire Horner‐Devine; John M. Drake; Sarah M. Emery; Joel M. Gramling; David B. Vandermast (Ecology Letters, 2004)
Ecologists have long sought to understand the relationships among species diversity, community productivity and invasion by non‐native species. Here, four long‐term observational datasets were analyzed using repeated measures statistics to determine how plant species richness and community resource capture (i.e. productivity) influenced invasion. Multiple factors influenced the results, including the metric used to quantify invasion, interannual variation and spatial scale. Native richness was positively correlated with non‐native richness, but was usually negatively correlated with non‐native abundance, and these patterns were stronger at the larger spatial scale. Logistic regressions indicated that the probability of invasion was reduced both within and following years with high productivity, except at the desert grassland site where high productivity was associated with increased invasion. Our analysis suggests that while non‐natives were most likely to establish in species rich communities, their success was diminished by high resource capture by the resident community.

Effects of environmental variation on extinction and establishment - John M. Drake; David M. Lodge (Ecology Letters, 2004)
Theoretical models predict that increasing environmental variation increases the probability of extinction, decreases the probability of establishment, and influences the distribution of times to extinction or establishment. We conducted an experiment with 281 independent populations of Daphnia magna under controlled laboratory conditions to test these predictions. Consistent with the theory, the fraction of populations going extinct increased and the fraction of populations establishing self‐sustaining populations decreased under higher levels of environmental variation compared with controls. Time to extinction decreased under higher levels of environmental variation, but we found no effect on time to establishment. These results are consistent with theoretical predictions from models of extinction. They therefore support the use of stochastic population models to predict the fates of introductions of non‐indigenous species or native endangered species based on historic fluctuations and/or expected future conditions.

Effects of elevated atmospheric CO 2 on root decomposition in a scrub oak ecosystem - John J. Dilustro; Frank P. Day; Bert G. Drake (Global Change Biology, 2001)
The effects of elevated atmospheric CO 2 on fine root decomposition over a 828‐day period were investigated using open top chambers with both ambient and elevated (700 ppm) CO 2 treatments in an oak–palmetto scrub ecosystem at Kennedy Space Center, Florida. Carbon dioxide enrichment of the chambers began 15 May 1996. The experiment included roots grown in ambient and elevated carbon dioxide. Vertical litterbags installed in September 1996 in each elevated and ambient chamber incubated from December 1996 to December 1998 showed no significant treatment effect on fine root or rhizome mass loss. Initial fine root percentage mass loss varied from 10.3% to 13.5% after three months; 55.5% to 38.3% of original mass had been lost after 828 days. A period of nitrogen immobilization occurred in both fine roots and rhizomes in the elevated CO 2 incubation, which is a potential mechanism for nitrogen conservation for this system in an elevated CO 2 world .

Comparison of a beet curly top virus isolate originating from the old world with those from the new world - Rob W. Briddon; Drake C. Stenger; Ian D. Bedford; John Stanley; Keramatollah Izadpanah; Peter G. Markham (European Journal of Plant Pathology, 1998)

Cytokinin pulse-mediated shoot organogenesis from cotyledons of Sitka spruce [Picea sitchensis (Bong.) Carr.] and high frequency in vitro rooting of shoots - P.M.W. Drake; A. John; J.B. Power; M.R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

Cloning and characterization of tomato leaf senescence-related cDNAs - Isaac John; Rachel Hackett; Wendy Cooper; Rachel Drake; Aldo Farrell; Don Grierson* (Plant Molecular Biology, 1997)